2015
DOI: 10.1115/1.4030057
|View full text |Cite
|
Sign up to set email alerts
|

Developing World Users as Lead Users: A Case Study in Engineering Reverse Innovation

Abstract: This paper examines the "reverse innovation" of the leveraged freedom chair (LFC), a high-performance, low-cost, off-road wheelchair originally designed for developing countries. A needs study of 71 developed world wheelchair users was conducted through three different data collection efforts. These data were contrasted with studies of 125 developing world wheelchair users, who were shown to be lead users for their developed world counterparts. The GRIT freedom chair (GFC), the developed world version of the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
0
21
0
2
Order By: Relevance
“…Users from developing countries can be also be considered as lead users. Innovation is traditionally linked to economic growth, competitiveness and progress (House, 2011;Judge et al, 2015) and often associated with developed countries. On the other hand, recognizing users from developing countries as lead users can be the key for reverse innovation as designers can understand their latent needs and create globally disruptive innovations by serving these markets (Judge et al, 2015).…”
Section: Characterizing the Lead Usersmentioning
confidence: 99%
“…Users from developing countries can be also be considered as lead users. Innovation is traditionally linked to economic growth, competitiveness and progress (House, 2011;Judge et al, 2015) and often associated with developed countries. On the other hand, recognizing users from developing countries as lead users can be the key for reverse innovation as designers can understand their latent needs and create globally disruptive innovations by serving these markets (Judge et al, 2015).…”
Section: Characterizing the Lead Usersmentioning
confidence: 99%
“…Corsi, Di Minin and Piccaluga (2014) explained that reverse innovation could be associated with internal resistance and the risks of cannibalizing its existing products. Judge et al (2015) analyzed how users from developing countries could be lead users in the confection of a wheelchair. Finally, Winter and Govindarajan (2015) highlighted some lessons for multinationals in terms of engineering reverse innovation.…”
Section: Reverse Innovation and Reverse Knowledge Transfermentioning
confidence: 99%
“…Hannukainen and H€ oltt€ a-Otto suggested that studying the needs of disabled users leads to the discovery of latent needs of ordinary users [14]. Judge et al proposed investigating users from the developing world to elicit latent needs of developed world users [15]. Srivastava and Shu studied Old Order Mennonites, who practice a low resource lifestyle, to gain inspiration for how to inspire the general population to live a more environmentally conscious lifestyle [16].…”
Section: Background On Lead Usersmentioning
confidence: 99%
“…Wolf and McQuitty asserted that the best examples of prosumers are the participants in a DIY movement [9]. While the design community has studied the lead user concept [2,4,[10][11][12][13][14][15][16][17], DIY practitioners have been overlooked, despite the fact that their characteristics closely resemble those of lead users.…”
Section: Introductionmentioning
confidence: 99%